La crisi del pensiero e il ritorno del problema del senso. Riflessioni sul significato filosofico della attuale ricerca neuro-cognitiva - Vanzago, Luca (Bollettino Filosofico, 2016)
This paper addresses the question concerning the crisis of thought from the standpoint of the renewal of interest for the notion of consciousness, produced by the developments in the field of neuroscience. Once a discredited notion, consciousness is making a clamorous comeback which however tends to polarize the debate and resuscitate old metaphysical battles. The neuro-cognitive approach, in particular, while undisputedly producing important contributions, tends to adopt a naïve materialist approach, which impoverishes the complexity of the phenomenon and thus contributes to the propagation of a conception of experience, which is growingly anti-humanistic. Yet other approaches are possible, which at once preserve the importance of scientific research and provide with different categories able to frame the scientific results in more fecund ways. Neuro-phenomenology is the best candidate in this sense, for it focuses on the importance of first-person perspective in a rigorous way.